Prevalence and Correlates of Comprehensive HIV/AIDS Knowledge among Women Aged 15–49 Years in Pakistan: Comprehensive HIV/AIDS Knowledge among Women Aged 15–49 Years in Pakistan - Siddique, Hira; Abbas, Saira; Rizwan Safdar, Muhammad; Atif Ayoub, Muhammad; Shahzad, Mahnoor (Pakistan Journal of Health Sciences, 2022)
Pakistan is ranked second among the countries in pacific Asia where the AIDS epidemic is spreading rapidly. Objectives: This study examines the comprehensive HIV/AIDS knowledge and measures the relationship between knowledge and socio-demographic characteristics of women aged 15-49 in Pakistan. Methods: It is based on secondary data analysis of the Pakistan Demographic and Health Survey 2017-2018. Data were collected from 50,495 married women aged 15-49 through the questionnaire. Descriptive statistics were applied to summarize the data while bivariate analysis was conducted to find out the correlations. Results: The study found that Pakistani women have a low level of knowledge regarding HIV/AIDS. Moreover, a significant relationship was found between comprehensive HIV/AIDS knowledge and wealth index as well as with the level of access to information. It shows that women from the richest households with moderate access to information had a high level of HIV/AIDS knowledge. Conclusions: Social stigmas regarding HIV/AIDS are rooted in Pakistani traditional society which is consequently the cause of the lack of knowledge regarding this epidemic among people in Pakistan